Flavonoids isolated from the flowers of Camellia chrysantha - Van, Nguyen Thi Hong; Bach, Pham Cao; Ich, Cam Thi; Phuong, Doan Lan; Thanh, Le Tat; Toan, Tran Quoc; Long, Pham Quoc (Vietnam Journal of Science and Technology, 2019)
Camellia chrysantha (the golden camellia, golden tea) is a species of evergreen shrub or small tree belonging to the family Theaceae. The flowers and the leaves of this plant are used as tea and drank for its health benefits. The aim of this study was to investigate the chemical constituents of the flowers of Camellia chrysantha. Five flavonoids were isolated from the flowers of Camellia chrysantha (Theaceae), including (+)-catechin (1), (-)-epicatechin (2), quercetin (3), quercetin-3-O-methyl ether (4) and kaempferol (5). Their chemical structures were elucidated by spectroscopic data analysis and by comparison with those reported in the literature. Among five compounds, compounds 4 was isolated for the first time from this species.